2016
DOI: 10.1515/cog-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

What corpus-based Cognitive Linguistics can and cannot expect from neurolinguistics

Abstract: This paper argues that neurolinguistics has the potential to yield insights that can feed back into corpus-based Cognitive Linguistics. It starts by discussing how far the cognitive realism of probabilistic statements derived from corpus data currently goes. Against this background, it argues that the cognitive realism of usage-based models could be further enhanced through deeper engagement with neurolinguistics, but also highlights a number of common misconceptions about what neurolinguistics can and cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…This and similar research (for a review see Blumenthal-Dramé, 2016) has shown that corpus-derived metrics can be tested against processing cost at different levels of language description, from orthography up to syntax. This makes it possible to adjudicate between competing metrics so as to identify the cognitively most pertinent and thus meaningful metrics for a given language.…”
Section: Complexity Metrics and Cognitive Researchmentioning
confidence: 85%
“…This and similar research (for a review see Blumenthal-Dramé, 2016) has shown that corpus-derived metrics can be tested against processing cost at different levels of language description, from orthography up to syntax. This makes it possible to adjudicate between competing metrics so as to identify the cognitively most pertinent and thus meaningful metrics for a given language.…”
Section: Complexity Metrics and Cognitive Researchmentioning
confidence: 85%
“…Chunk status does not only influence the production of sequences in different modalities; it also modulates how observers and comprehenders segment the incoming sensory signal. For example, high-frequency chunks are both more difficult to segment and more expected than lower-frequency sequences (Blumenthal-Dramé, 2012, 2016a, 2016bBlumenthal-Dramé et al, 2017).…”
Section: Effects Of Repetition Across Domainsmentioning
confidence: 99%
“…Surprisal and entropy reduction have both been shown to be good predictors of processing cost across different levels of language description, from morphology via the levels of lexical combinatorics up to syntax (Blumenthal-Dramé, 2016b;Blumenthal-Dramé et al, 2017;McConnell & Blumenthal-Dramé, 2018).…”
Section: Information Transfer Measures In Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…But a stimulus may also cause surprise by virtue of deviating from a cognitive ground, e.g., when violating social or probabilistic expectations (Clark, 2013 ). This has prompted researchers to examine the relationship between expectations and the perceptual salience of linguistic stimuli in new ways (Hanulíková et al, 2012 ; Rácz, 2012 ; Hanulíková and Carreiras, 2015 ; Blumenthal-Dramé, 2016a , b ; Roller, 2016 ; Blumenthal-Dramé et al, 2017 ), and inspired us to organize a workshop devoted to this particular area.…”
mentioning
confidence: 99%